(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This section features the need of logical parallel computing to take care of complex logical issues like Genome sequencing, plan of nuclear bomb, reemergence directions of room vehicles and so forth that interest huge scope calculations. Numerous logical projects are likewise recorded that were started to foster such huge foundation. This prompted the advancement of different models for communication technologies therefore today the calculation rates of logical parallel computers are seen to have outperformed the peta FLOPS mark. The part makes a critical blemish on the Indian commitments to the advancement of communication technologies in logical parallel computing particularly the Floswitch at the Flosolver lab of National Aerospace Laboratories, Bangalore. The part closes with the notice on arising difficulties, new standards and conceivable outcomes in the advancement of the Floswitch.